Staying or leaving? Teacher professional characteristics and attrition in Arizona traditional public and charter schools - Pivovarova, Margarita; Powers, Jeanne M. (Education Policy Analysis Archives, 2022)
In this study, we analyzed public school teacher employment data from 2009 to 2015 to understand why teacher attrition is 54% higher in charter schools compared to traditional public schools. We investigated the factors associated with the differences in exit rates of teachers from traditional public and charter schools in Arizona which has a large charter school sector. Our findings suggest that the major factors behind the gap in retention rates between school sectors in Arizona are teachers’ professional characteristics: less experienced teachers and teachers with alternative certification are more likely to exit schools and, in particular, charter schools which also employ a significantly larger share of these teachers. We argue that charter school and school district leadership might consider interventions, mentoring, and support for teachers in the early stages of their career targeted at novice teachers.